1955
DOI: 10.1002/zaac.19552810302
|View full text |Cite
|
Sign up to set email alerts
|

Über die Konstitution der sauren Sulfite. I. Wäßrige Disulfit‐(Pyrosulfit‐)Lösungen und ihr Verhalten in Abhängigkeit von Konzentration und Alkalisierungsgrad

Abstract: Es werden Apparaturen beschrieben, die es gestatten, luftempfindliche wäßrige Lösungen unter völligem Ausschluß von Sauerstoff herzustellen, zu spektroskopieren und zu analysieren. Untersuchungen an Natrium‐ und Kaliumdisulfitlösungen (‐pyrosulfitlösungen) ergeben, daß Kationen am Schwingungsvorgang nicht beteiligt sind. Durch Verdünnungs‐ und Alkalisierungsversuche wird gezeigt, daß die kräftige Frequenz bei 423 cm−1 nicht einer SS‐Bindung eines S2O 52 ‐Ions zugehören kann, daß jedoch mehrere Ionenarten nebe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1956
1956
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Dimerisation of hydrogen sulfite has been investigated in aqueous solution by conductometry, 32 as well as IR, 12,33 UV [6][7][8][9][10]34 and Raman 10,11,[35][36][37][38] spectroscopic techniques. Table 1 summarises the reported values for the dimerisation constant, K D , in the literature.…”
Section: And 4 and References Therein)mentioning
confidence: 99%
“…Dimerisation of hydrogen sulfite has been investigated in aqueous solution by conductometry, 32 as well as IR, 12,33 UV [6][7][8][9][10]34 and Raman 10,11,[35][36][37][38] spectroscopic techniques. Table 1 summarises the reported values for the dimerisation constant, K D , in the literature.…”
Section: And 4 and References Therein)mentioning
confidence: 99%
“…If the contribution of the second order exchange under conditions where we do. This process R2 = k2 [HS03-l2 is subtracted from the discrepancy we Suggest is probably due to the low total rate of exchange [6] using the value of k2 sensitivity of the methods used by those workers deduced from Fig. 4, then k-, can be determined (who followed the isotopic com~osition of the from eq.…”
Section: Rate Law and Meclzanisrn For Exchangementioning
confidence: 99%
“…40 The extensive vibrational spectroscopy studies conducted by Simon and Waldman revealed the presence of bisulte anion (HSO 3 À ), which resulted from the dissolution of SO 2 in water. [41][42][43][44][45] In addition, it has been proven that the existence of NH 3 in hydrated SO 2 clusters accelerates the production of HSO 3…”
Section: Introductionmentioning
confidence: 99%